Does capitation affect patient satisfaction and prevalence of out-of-pocket payments in the insured? A propensity score analysis of Ghana's demographic and health survey data - Shafiq Siita; Sharon E. Cox; Kara Hanson (BMC, 2019)
Abstract Background Ghana's National Health Insurance Scheme (NHIS) piloted capitation payment for primary care services in the Ashanti region from 2012 to 2017. Capitation was piloted as a means of cost containment but also to induce managed competition among health providers to improve the responsiveness of healthcare delivery. This study examined the effects of exposure to capitation on perceived health service quality and prevalence of out-of-pocket payments in NHIS insured clients. Methods Respondents of the 2014 Ghana Demographic and Health Survey (G-DHS) who reported having a valid NHIS card as their only form of health insurance coverage and made a health facility visit within the 6 months prior to the survey were used to assess the exposure effects of capitation on four outcomes: overall patient satisfaction, perceived friendliness of health staff, perceived adequacy of consultation time, and prevalence of out-of-pocket payments. We applied propensity score matching to balance distributions of covariates and to compare outcomes between exposed NHIS insured clients and their unexposed counterparts. Results NHIS insured clients exposed to capitation had 10 percentage points higher probability of encountering out-of-pocket payments than their unexposed counterparts (p = 0.009; 95% CI: 2.5-17.8%). There was no evidence of a difference between the two exposure groups for ratings of the three quality perceptions outcomes examined: overall patient satisfaction, difference 0.63 units (p = 0.46); perceived friendliness of health staff, difference 1.1% (p = 0.50); and perceived adequacy of consultation times, difference 0.1% (p = 0.96). Conclusion In the Ghanaian context, our results suggest capitation was associated with a greater probability of out-of-pocket payments and no difference in perceived service quality. Future research should examine clinical quality of healthcare and how much out-of-pocket payment occurred under capitation.